A study of obesity drivers in Mexico using alternative future scenarios to define policy, - Anguiano Arreola, Paulina (Cranfield University, 2022)
In the last four decades, Mexico has experienced a rise in the prevalence of obesity among urban households, increasing the risks of comorbidities and premature deaths. This PhD thesis examines what is driving obesity in urban Mexican households to develop a systemic understanding of consumers’ eating choices and health behaviours and how these drivers interact and change eating choices and dietary behaviours under alternative future scenarios. This analysis leads to a discussion about potential policy implications to encourage healthier eating choices and improve dietary patterns. The largely qualitative research comprised: 1. A broad literature review to identify drivers of obesity, using a Social, Technological, Economic, Environmental, Political, Legal and Ethical (STEEPLE) framework to identify a broader range of external drivers influencing individuals’ eating choices in Mexico. 2. A theoretical framework that combines the Theory of Planned Behaviour (TBP) and Social Cognitive Theory (SCT) to encompass the impact of external and internal factors that influence eating choices. 3. A survey to understand individuals’ eating behaviours and the impact on nutrition from a selected sample of the population in Mexico. 4. The development of scenarios to deliver plausible futures in the context of consumer’s behaviour, eating choices and impact on obesity in Mexico. The results showed the importance of multidisciplinary collaboration within the system that can breach the pre-existing gaps between the education, health, and food production sectors. In addition, the findings confirmed the influence of eating choices associated with food insecurity, driven in part by social inequalities and political and legal agreements, which influence internal behaviours and impact health. In addition, scenario development results suggested the need to support community/regional food production projects, re-evaluation of current initiatives, integration of multiple sectors to enhance collaborations, higher transparency in the developed initiatives. The measures can a) increase economic, education, and employment opportunities; b) improve sociodemographic equality; c) improve health literacy; and d) promote food security. Main contribution of this research was a more holistic and improved perspective of consumers’ eating choices and health behaviours through the visualisation of a systemic understanding, derived from selected methods of literature, theoretical framework, consumer survey and scenarios to set the connections between external and internal drivers.
Garnett, Kenisha - Associate Supervisor
Keywords: STEEPLE; cognitive dissonance/value-action gaps; eating choices; sociodemographic inequality; food policy; systemic understanding